The Phenomenon Marriage is Scary: Causal Factors and Efforts Faced by Muslim Communities in Indonesia - Sulfinadia, Hamda; Jurna Petri Roszi; Mega Puspita; A'zizil Fadli; A'inil Fadli (AL-ISTINBATH : Jurnal Hukum Islam, 2025)
This research focuses on the phenomenon marriage is scary that has become a phenomenon in Indonesia. Indonesian statistics show that the marriage rate is decreasing, and the divorce rate is increasing every year.  It was found that as many as 397 Muslims in Indonesia experienced marriage is scar. This may be one of the causes of the declining marriage rate every year.  This study aims to determine and analyze the causes of marriage is scary and explore the efforts made in the internal and external environment. This study is a qualitative research, primary data comes from respondents who experience marriage is scary, parents, traditional leaders and religious leaders, totaling 20 people. The findings of this study indicate that first, the causes of marriage is scary in Indonesian Muslim communities are economic factors (31.99%), customs and culture (15.62%), social media (6.8%), domestic violence (15.60%), social media (6.85) and other reasons (11.44%); Second, the efforts made to minimize the occurrence of marriage is scary in Indonesia are approaches and open communication with families, providing religious strengthening and understanding of marriage and strengthening local wisdom.